Take filtering capability's intelligent double -cabin solar water heater - XU JIANPING (2018)
The utility model discloses a take filtering capability's intelligent double -cabin solar water heater, including installation box, hot -water tank, cold water storage cistern, lifter and thermal -collecting tube mounting bracket, intermediate position department of the internal portion of install bin installs the rose box, the cold water storage cistern is installed to rose box one side, the hot-water tank is installed to the rose box opposite side, the rose box is including filtering the box, that filters that the box leads to the installation of subcooled water case upper end advances water piping connection install bin body surface face, filter the box lower extreme and install the concentrated pipe, the connecting pipe is installed to the concentrated pipe lower extreme, the connecting pipe is close to one side of cold water storage cistern and installs the cold water storage cistern valve, the connecting pipe is close to one side of hot -water tank and installs the hot -water tank valve, the thermal -co